Hybrid Solar Heat Pump Dryer for Marine Products - Amir, Abdul Razak (Faculty of Mechanical & Automotive Engineering Technology, 2022)
The primary economic activity around Kuala Pahang in Pekan focuses on fisheries and processed marine-based products, mainly the dried salted fish and seafood.